Implementasi Program Ekstrakurikuler Robotik dalam Meningkatkan Kreativitas Peserta Didik di Min Doko Kediri - Al Imatus Solikha; Marita Lailia Rahman; Ahmad Ali Riyadi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Robotic extracurricular activities have the potential to develop students' creativity. The implementation of robotics extracurricular programs in improving students' creativity is an activity or activity that is determined outside of class hours, usually aimed at expanding students' insight or knowledge and skills related to technology, operation or development of human machines and human machine systems. The purpose of this study is to describe the design, process, and assessment of robotics extracurricular programs in improving students' creativity at MIN 2 Kediri. This research is a qualitative research with a case study research type. Data collection techniques use interviews, observation, and documentation. Meanwhile, for data analysis, researchers perform data reduction, data presentation, and drawing conclusions. This study produces findings that the robotics extracurricular program in improving students' creativity at MIN 2 Kediri has been running effectively. The methods used in the robotics extracurricular program are the PjBL method, STEM, demonstration, and practice.